PENGARUH LATIHAN PASSING BAWAH DUA LENGAN TERHADAP KEMAMPUAN PASSING BAWAH TIM BOLAVOLI PUTRI SMPN 24 PEKANBARU - Meirida Putri; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Issues raised in this study is that the passing skills down yet so good. This is evident from some of the matches have been followed as the match between the level of schools in Pekanbaru, as well as in the match National Student Sports Olympiad (O2SN) secondary school level first to be held each year. Women's volleyball team SMP 24 Pekanbaru at the time of passing down not so optimal, such as: 1. The passing was not until keteman, 2. The ball does not go up while doing passing under, 3. Movement rudimentary when making passing below. This research is a study with experimental treatment (Experimental), the population in this study is SMPN 24 Pekanbaru. sample in this study is a population which numbered 12 people. The technique can capture data from the pre-test and post-test. The instruments used in this research is to test passing down to the wall, which aims to measure the ability of passing down. As the independent variable is the practice of passing under the two arms (X), while the dependent variable is below the passing ability (Y). After that, the data is processed with statistical, normality test with Liliefors test at significant level 0,05α. The hypothesis is the effect of exercise are passing under the two arms of the ability of passing down. Based on t test analysis produces Thitung of 4.024 and 1.796 Ttabel means Thitung> Ttabel. It can be concluded that Ha is accepted, it concludes that there is significant influence from passing drills under the two arms of the ability of passing down the volleyball team SMPN 24 Pekanbaru.Key Words: Passing Drills Down